FENOMENA POLIGAMI ANTARA SOLUSI SOSIAL DAN WISATA SEKSUAL DALAM ANALISIS HUKUM ISLAM, UU NO. 1 TAHUN 1974, DAN KHI - Moh. Faizur Rohman; Muhammad Solikhudin (AL-HUKAMA, 2017)
Abstract: Polygamy is one of the problem in the marriage of the most discussed widely and controversial. One side of polygamy is rejected with a variety of arguments between normative, psychological, even always associated with gender injustice-as revealed by gender activists or activists of women. In fact, Western writers often claim that polygamy is evidence that the teaching of Islam in the areas of marriage is very discriminatory against women. On the other side, polygamy campaigned as it is considered as one alternative to resolve the phenomenon of cheating and prostitution. Whatever the reasons said, clearly polygamy is a religion shari'ah presence clearly in the Qur'an, regardless of how this verse applied. The issue is under what conditions and by whom this polygamy shari'ah can be implemented. This paper attempts to examines polygamy on one side of the impact on social solution, on the other side can be regarded as sexual tourism which is conducted the husband, and could also both reasons join simultaneously. Furthermore, the authors discuss polygamy with analysis knife of Islamic Law, Law No. 1 of 1974, and KHI (Positive Law). Not only that, the authors also attempt to align polygamy study it with a knife of analysis the theory of phenomenology in sociology. Keywords: polygamy, Islamic Law, Positive Law, Phenomenology.